The Correlation Between Language Learning Strategies and Students’ Thinking Styles of IAIN Langsa - Muslem; Wati, Shafrida; Devi Siregar , Sagita (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2022)
This study was the correlation between language learning strategies and students’ thinking styles. This study aimed to determine whether there is a significant correlation between language learning strategies and student thinking styles. This study used a quantitative correlational approach as a research method. The data were collected by Likert scale questionnaire. The research data were analyzed using SPSS 26.0 program. This program was used to find out whether there is a significant correlation between language learning strategies (X) and students‟ thinking styles (Y). The result of the questionnaire showed there is a positive correlation between language learning strategies and student thinking styles. It can be proved by the correlation coefficient (r count) and significance value (ρ) got from the calculation r count = 0.507, ρ = 0.002 < 0.05. Based on the findings of the data analysis, there is positive significant relationship between language learning strategies and student thinking styles of students’ English education department IAIN Langsa.